Analisis Nisbah Bagi Hasil Pembiayaan Mudharabah pada Bank Syariah Mandiri KCP Sengkang - Ainul Hikmah; Nahariah Nahariah (Jurnal Ilmiah Al-Tsarwah : ilmu ekonomi dan keuangan (konvensional dan syariah), 2019)
The purpose of this research is to understand the meaning of revenue sharing, the method of calculating revenue sharing and the profit sharing advantage on mudharabah financing in independent Islamic banks. The results of the study show that Revenue Sharing is a profit sharing system that is calculated from the total revenue of fund management without being reduced by the cost of managing funds. So if the bank and the customer use the mudharabah scheme in carrying out working capital financing, if the business is profitable, then it must be divided based on the profit sharing portion. The advantages of mudharabah financing sharing ratio in Bank Syariah Mandiri Sengkang KCP is to be able to increase investment in third party funds on Islamic banks because if the bank uses a profit sharing calculation system based on revenue sharing where profit sharing will be distributed from total revenues before deducting with costs, the likelihood that there will be a profit sharing rate that will be received by the owner of the fund will be greater than the prevailing market interest rate.